2004
DOI: 10.1113/jphysiol.2004.061416
|View full text |Cite
|
Sign up to set email alerts
|

Burst generation in rat pyramidal neurones by regenerative potentials elicited in a restricted part of the basilar dendritic tree

Abstract: The common preconception about central nervous system neurones is that thousands of small postsynaptic potentials sum across the entire dendritic tree to generate substantial firing rates, previously observed in in vivo experiments. We present evidence that local inputs confined to a single basal dendrite can profoundly influence the neuronal output of layer V pyramidal neurones in the rat prefrontal cortical slices. In our experiments, brief glutamatergic stimulation delivered in a restricted part of the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 61 publications
(88 reference statements)
3
134
0
Order By: Relevance
“…Intracellular voltage-sensitive dyes cannot be used to determine the absolute amplitude (in mV) of the electrical transients in distal dendritic segments (Antic, Major & Zecevic, 1999). However, voltage-sensitive dyes can be used to detect a relative amplitude change between signals obtained from the same dendritic segment in consecutive recording trials (Milojkovic et al, 2004). Since the concentration and partition of the voltage-sensitive dye in a given dendritic segment is unlikely to change significantly within a 2-3 min period, the sensitivity of voltage-sensitive dye measurements obtained from the same dendritic segment remains constant between successive recordings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intracellular voltage-sensitive dyes cannot be used to determine the absolute amplitude (in mV) of the electrical transients in distal dendritic segments (Antic, Major & Zecevic, 1999). However, voltage-sensitive dyes can be used to detect a relative amplitude change between signals obtained from the same dendritic segment in consecutive recording trials (Milojkovic et al, 2004). Since the concentration and partition of the voltage-sensitive dye in a given dendritic segment is unlikely to change significantly within a 2-3 min period, the sensitivity of voltage-sensitive dye measurements obtained from the same dendritic segment remains constant between successive recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Quite the opposite is true for glutamate-evoked dendritic plateau potentials. Dendritic plateau potentials, which originate in the same section of the basal dendrite as fast spikes, provide a very reliable drive for bursts of action potentials (Milojkovic et al, 2004). The second piece of evidence against basal spikes acting as precise temporal encoders consists of in vivo recordings of fast prepotentials.…”
Section: The Functional Role Of Basal Spikeletsmentioning
confidence: 99%
See 2 more Smart Citations
“…By directly comparing the amplitude of excitatory postsynaptic potentials (EPSPs) with the back-propagating action potential at different dendritic locations, it was concluded that EPSPs undergo only slight attenuation as they propagate from their site of origin in the glomerular tuft to the soma. Internal application of voltage-sensitive dyes has also been used to study regenerative plateau potentials [38,39] and local dendritic sodium spikes [40] in basal dendrites in cortical pyramidal neurons. A recent study also used internally Fig.…”
Section: Voltage Imaging Using Internally Applied Dyesmentioning
confidence: 99%